Osteochondritis dissecans of the humeral trochlea in two pediatric athletes: two cases and review of literature - Yakkanti, Ramakanth; Quintero, Daniel; Southworth, Cole; Kaplan, Lee; Jose, Jean (Brazilian Journal of Case Reports, 2021)
We herein report two unusual cases of osteochondritis dissecans (OCD) of the trochlea. The injury consisted of a focal alteration of subchondral bone secondary to repetitive micro trauma from overhead maneuvers (pitching) in two male adolescents. Only 23 other cases of OCD affecting the trochlea have been reported. We comment on this discrepancy, explore the radiographic features, and detail the non-operative management that was undertaken. We substantiate our report with a systematic review of all OCD cases of the trochlea and provide information on patient demographics, sport type, management, recuperation and finally significance of radiographic grading.